Mathematics of evolution and phylogeny - Gascuel, Olivier, 1956- (Oxford University Press, 2005)
"This book considers evolution at different scales. The focus is on the mathematical and computational tools and concepts, which form an essential basis of evolutionary studies, indicate their limitations, and give them orientation"--Provided by publisher.